Удосконалення конструкції компактного 3D-принтера - Коцар, Роман Олегович; Kotsar, Roman Olehovych (Національний університет "Львівська політехніка", 2024)
Дипломна робота присвячена проєктуванню та техніко-економічному обґрунтуванню сучасного обладнання для 3D друку пластиком різного типу. Робота включає пояснювальну записку та графічну частину. Пояснювальна записка структурована на вступ, технологічну та конструкторську частини, а також додатки, що містять економічне обґрунтування, розділ з охорони праці та специфікації до графічної частини. У технологічній частині досліджено основні етапи сучасних технологій тривимірного друку та технологічного процесу 3D друку, SLA, SLS, LOM, 3DP та FDM, наведено аналіз сучасного обладнання. Для кожної технології розглянуто принцип роботи, типи витратних матеріалів, основні переваги та недоліки, що дозволило сформувати комплексне уявлення про їх можливості та обмеження. Розглянуто принципи роботи машин, що використовуються на цих етапах. Конструкторська частина містить опис будови та принципу дії 3D принетра та аналогів. Виконано розрахунки кінематичної схеми 3D притера, потужності її приводу, а також механічних передач. Було проаналізовано точності розмірів заготовок по кривих, що виготовляються на даному 3D-принтері.розподілу; виконано корекцію точності даного принтера; налаштовані криві нормального розподілу; розрахований довірчий інтервал для кожного розміру. У розділі економічного обґрунтування проведено аналіз витрат на виготовлення обладнання, оцінено економічний ефект від його впровадження у виробничий процес. Обґрунтовано доцільність впровадження запропонованого технічного рішення у промислове виробництво, з урахуванням потенційного зниження енерговитрат та підвищення продуктивності. Також розроблено заходи з охорони праці для забезпечення безпечних умов експлуатації обладнання. Запропоновано рішення, які сприяють зменшенню професійних ризиків під час роботи з машинами для 3D друку. Графічна частина містить загальний вигляд машини для 3D друку, складальне кресслення та деталювання її конструктивних елементів, а також специфікації до складальних креслень.

The thesis is devoted to the design and feasibility study of modern equipment for 3D printing with different types of plastic. The work includes an explanatory note and a graphic part. The explanatory note is structured into an introduction, technological and design parts, as well as appendices containing an economic feasibility study, a section on occupational safety, and specifications for the graphic part. The technological part describes the main stages of modern 3D printing technologies and the 3D printing process, SLA, SLS, LOM, 3DP and FDM, and provides an analysis of modern equipment. For each technology, the principle of operation, types of consumables, main advantages and disadvantages are considered, which allowed to form a comprehensive picture of their capabilities and limitations. The principles of operation of the machines used at these stages are also considered. The design part contains a description of the structure and principle of operation of the 3D printer and analogues. Calculations of the kinematic scheme of the 3D printer, its drive power, and mechanical gears were performed. The accuracy of the dimensions of the workpieces according to the curves produced by this 3D printer was analysed. distribution; the accuracy of this printer was corrected; normal distribution curves were set up; and the confidence interval for each size was calculated. The design part contains a description of the structure and principle of operation of the 3D printer and analogues. Calculations of the kinematic scheme of the 3D printer, the power of its drive, and mechanical gears were performed. The accuracy of the workpiece dimensions according to the curves produced by this 3D printer was analysed. distribution; the accuracy of this printer was corrected; normal distribution curves were adjusted; and the confidence interval for each size was calculated. In the section on economic justification, the article analyses the costs of manufacturing the equipment and estimates the economic effect of its introduction into the production process. The feasibility of implementing the proposed technical solution in industrial production is substantiated, taking into account the potential reduction of energy consumption and increase in productivity. Labour protection measures have also been developed to ensure safe operating conditions for the equipment. Solutions have been proposed to reduce occupational risks when working with 3D printing machines. The graphic part contains a general view of the 3D printing machine, assembly drawings and details of its structural elements, as well as specifications for assembly drawings.
Іmproving the design of a compact 3D printer
Keywords: 6.133.00.00; філамент; 3D друк; принтер; заготовка; привод; автоматизація; filament; 3D printing; printer; work piece; drive; automation